2018
DOI: 10.1055/s-0037-1609869
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Conformational Analysis of 10-Mesitylanthracene-1,8-diyl Oligomers

Abstract: Oligomers consisting of 10-mesitylanthracene-1,8-diyl units were synthesized by Ni-mediated coupling of the corresponding dibromide as new oligoarene compounds. The structures and properties of these oligomers were investigated by NMR and electronic spectroscopy. Conformational analyses with the aid of DFT calculations revealed that each biaryl axis adopted a nearly perpendicular conformation, and the trimers and tetramers existed as a mixture of diastereomeric conformers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The analysis gave the rate of enantiomerization at 5.7×10 −6 s −1 at 40 °C corresponding to the activation free energy of Δ G ≠ 298 108 kJ mol −1 (Figure S17). This barrier was higher than those of Nap 2 (98 kJ mol −1 ) [3] and 1,1′‐ Ant 2 (96 kJ mol −1 ) [8f,g] . These data indicated that the barriers were slightly enhanced by the fusion of additional aromatic moieties relative to Ant 2 .…”
Section: Resultsmentioning
confidence: 77%
“…The analysis gave the rate of enantiomerization at 5.7×10 −6 s −1 at 40 °C corresponding to the activation free energy of Δ G ≠ 298 108 kJ mol −1 (Figure S17). This barrier was higher than those of Nap 2 (98 kJ mol −1 ) [3] and 1,1′‐ Ant 2 (96 kJ mol −1 ) [8f,g] . These data indicated that the barriers were slightly enhanced by the fusion of additional aromatic moieties relative to Ant 2 .…”
Section: Resultsmentioning
confidence: 77%